The Analytics of SVARs: A Unified Framework to Measure Fiscal Multipliers - Caldara, Dario; Kamps, Christophe (Review of Economic Studies, 2017)
Does fiscal policy stimulate output? Structural vector autoregressions have been used to address this question, but no stylized facts have emerged. This paper makes two contributions. First, I derive analytical relationships between the output elasticities of tax revenue and government expenditures, and fiscal multipliers. I show that different priors about elasticities implied by the identification schemes generate a large dispersion in the estimates of tax and spending multipliers. Second, I estimate fiscal multipliers consistent with prior distributions of the elasticities computed by a variety of empirical strategies, and by employing a simple dynamic stochastic general equilibrium model. I document three findings for the U.S. for the period 1947-2010. First, the impact tax multiplier is close to 0. Second, the impact spending multiplier ranges between 0.35 and 1. Third, the probability that the spending multiplier is larger than the tax multiplier is above 0.8, for up to four years after policy interventions.